Comprehensive Design and Optimization of Brushless Direct Current Motor for the Desired Operating Conditions - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2021)
Brushless direct current (BLDC) motor which is widely preferred due to its high efficiency and low maintenance requirements, is commonly used in the aviation industry, robotic systems, and electric vehicles. In this study, dimensions and their interdependencies of BLDC motor were calculated, analysed, and optimized. At first, experiments and simulations have been carried out to obtain reference parameters. Afterward, slot dimensions have been studied in particular. After checking that the experimental data and simulation data are compatible, optimization studies were carried out. In addition, magnet thickness, skewness, magnet type, embrace and steel type were parametrically investigated in detail. As a result, the improved efficiency value as well as effect of the rated parameters on the efficiency was successfully determined and ssimulation results accomplishing performance characteristics were presented. © 2021 IEEE.
Keywords: ANSYS/Maxwell; BLDC motor; Design; Efficiency